(untitled) (Philosophy and Progress, 2021)
18th century Europe had produced many enlightened scholars. Voltaire was one of them. French Revolution was a great chapter in the history of France. It had made a new era in France. This epoch-making event had brought many significant changes in various sectors in France. It occurred in France but it not only changed France, it brought about a change in the whole world later on. It started in 1789 and continued till 1799. French philosopher Voltaire died in 1778. But his influence was profound. He had contributed to bring revolutionary changes in French church and governmental system through his writings. French revolutionaries were inspired by his wonderful literary works. French revolution and Voltaire are inseparably connected. In this article an attempt has been made to review the impact of Voltaire’s write-up in the mind of the French revolutionaries. Philosophy and Progress, Vol#65-66-; No#1-2; Jan-Dec 2019 P 145-162